Principles of taxation : advanced strategies - Jones, Sally M. and Rhoades, Shelly C. (Boston, MA : McGraw-Hill/Irwin, 2002)
"This book is ideal for students who studied principles of taxation for business and investment planning in their introductory course. The two textbooks provide an integrated two-semester sequence of topics that present a complete educational package for tax students".
Includes glossary, appendixes and index.
English text.
Latest issue consulted: 2003 ed.
Keywords: Business enterprises -- Taxation -- Law and legislation -- United States -- Periodicals; Tax planning -- United States -- Periodicals; Business enterprises -- Taxation -- Law and legislation; Tax planning; United States; Periodicals